Financial Literacy, Fintech Adoption, and the Financial Performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Sugianto; Maria Lusiana (Journal of Management, 2026)
This study examines the influence of financial literacy and financial technology (fintech) adoption on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. MSMEs constitute the backbone of the Indonesian economy, yet many continue to face constraints in accessing formal financial services and managing financial resources effectively. Using a quantitative approach with data collected from 150 MSME owners across West Java through a structured questionnaire, this study applies multiple linear regression to test the proposed hypotheses. The results indicate that both financial literacy and fintech adoption have a positive and significant effect on MSME financial performance, with fintech adoption showing a slightly stronger influence. These findings suggest that policies aimed at improving financial literacy and expanding access to digital financial services can meaningfully strengthen the resilience and growth of MSMEs. The study contributes to the growing body of literature on digital financial inclusion in emerging economies and offers practical implications for policymakers, financial institutions, and MSME actors.